A Minimally Invasive and Highly Effective Extracorporeal CO2 Removal Device Combined With a Continuous Renal Replacement Therapy. Issue 5 (19th January 2022) - Zanella, Alberto; Pesenti, Antonio; Busana, Mattia; De Falco, Stefano; Di Girolamo, Luca; Scotti, Eleonora; Protti, Ilaria; Colombo, Sebastiano Maria; Scaravilli, Vittorio; Biancolilli, Osvaldo; Carlin, Andrea; Gori, Francesca; et al.
Abstract : OBJECTIVES: Extracorporeal carbon dioxide removal is used to treat patients suffering from acute respiratory failure. However, the procedure is hampered by the high blood flow required to achieve a significant CO2 clearance. We aimed to develop an ultralow blood flow device to effectively remove CO2 combined with continuous renal replacement therapy (CRRT). DESIGN: Preclinical, proof-of-concept study. SETTING: An extracorporeal circuit where 200 mL/min of blood flowed through a hemofilter connected to a closed-loop dialysate circuit. An ion-exchange resin acidified the dialysate upstream, a membrane lung to increase Pco 2 and promote CO2 removal. PATIENTS: Six, 38.7 ± 2.0-kg female pigs. INTERVENTIONS: Different levels of acidification were tested (from 0 to 5 mEq/min). Two l/hr of postdilution CRRT were performed continuously. The respiratory rate was modified at each step to maintain arterial Pco 2 at 50 mm Hg. MEASUREMENTS AND MAIN RESULTS: Increasing acidification enhanced CO2 removal efficiency of the membrane lung from 30 ± 5 (0 mEq/min) up to 145 ± 8 mL/min (5 mEq/min), with a 483% increase, representing the 73% ± 7% of the total body CO2 production. Minute ventilation decreased accordingly from 6.5 ± 0.7 to 1.7 ± 0.5 L/min. No major side effects occurred, except for transient tachycardia episodes. As expected from the alveolar gas equation, the natural lung Pao 2 dropped at increasing acidification steps, given the high dissociation between the oxygenation and CO2 removal capability of the device, thus Pao 2 decreased. CONCLUSIONS: This new extracorporeal ion-exchange resin-based multiple-organ support device proved extremely high efficiency in CO2 removal and continuous renal support in a preclinical setting. Further studies are required before clinical implementation.